Health researchers’ voluntary science-communication with non-academics: motivations, barriers, and practices - Schøning, Bente; Sandanger, Torkjel M.; Rosenbaum, Sarah E.; Wien, Charlotte (Frontiers in Communication, 2025)
IntroductionThis study investigates the motivations, practices, and barriers encountered by health researchers in Norway when engaging in science communication with non-academic audiences. Given the legal mandate for public science communication in Nordic universities, understanding these dynamics is crucial for enhancing the quality and impact of research dissemination.MethodsThe research was conducted at UiT Arctic University of Norway and involved semi-structured interviews with 14 active health researchers from various disciplines. A realist thematic analysis was employed to identify key themes related to user-involvement practices, motivational factors, and communication barriers. Participants were selected based on their active engagement in science communication, and data were collected through interviews conducted in Norwegian.ResultsThe analysis revealed three main themes. First, researchers often employ user-involvement strategies throughout the research process, although communication of final results tends to revert to one-way dissemination. Second, motivations for engaging in science communication include a sense of duty to the public, career-enhancing visibility, and personal satisfaction. Third, barriers such as negative media experiences and lack of institutional support hinder effective communication. Researchers expressed a need for more robust institutional support, including resources for engaging with users and incentives for non-academic communication.DiscussionThe findings underscore the importance of institutional support in facilitating effective science communication. By providing resources and incentives, institutions can enhance the quality and impact of communication efforts, ensuring that research findings are accessible and relevant to the public. The study highlights the need for a shift from one-way dissemination to more participatory communication models, which can improve public engagement and knowledge uptake. Addressing barriers such as negative media experiences and lack of support is crucial for empowering researchers to communicate effectively.ConclusionThis study provides valuable insights into the dynamics of science communication in the health sector, offering recommendations for institutions to enhance support for researchers. By addressing identified barriers and implementing supportive measures, universities can empower researchers to effectively communicate their findings to non-academic audiences, thereby fulfilling their public engagement obligations and improving the societal impact of their research.